“Pay-as-you-wish” Program As Marketing Communication Strategy Using SOSTAC On Indonesian MSME Business - Syahrul Syahrul; Yohannes Don Bosco Doho; Yasinta Dewi Pradina (Journal of Research on Business and Tourism, 2022)
This project discusses the “Pay-as-you-wish” program as a marketing communication strategy using SOSTAC on Indonesian micro small and medium business enterprises study case in Omnivour. Omnivour, as one of the MSME brands, offers delivery affordable healthy food catering for its customers during Covid-19 pandemic as its business model. However, the brand still lacks awareness. Omnivour is facing the real problem that the operation should run for "big mass and big volume." The orders are still under the market size target of its brand expected. This project aims to implement the “Pay-as-you-wish” program as its marketing communication strategy. In elaborating the project planning, it uses the SOSTAC to determine the applicability of the Pay-as-you-wish programs being implemented as a marketing communication strategy for MSME business. Besides, it also sees the program's applicability as a treatment boost for the sale volume and brand awareness. The project was held for one month in October 2021, following the operational time of Omnivour. The project has been evaluated based on the metrics of this project objective.